(untitled) (Research, Society and Development, 2021)
Objective: To quantify the quassinoids of P. sprucei, a medicinal plant that is native to the Amazon region, using qNMR and investigate the inhibitory potential of isobrucein B and neosergeolide on the 3CLpro and RdRp targets of SARS-CoV-2 through in silico approaches. Methods: the quantification was performed in a fraction (F2-F3) enriched with the quassinoids isobrucein B and neosergeolide using the PULCON method. In silico assays were performed using molecular docking to assess interactions and binding affinity between neosergeolide and isobrucein B ligands with SARS-CoV-2 3CLpro and RdRp targets, and online servers were used to estimate pharmacokinetic and toxicity. Results: It was possible to determine the quantity of the two quassinoids isobrucein B and neosergeolide in the F2-F3 fraction (769.6 mg), which were present in significant amounts in the PsMeOH extract (5.46%). The results of the docking analysis, based on the crystallized structures of RdRp and 3CLpro, indicated that isobrucein B and neosergeolide are potential inhibitors of the two proteins evaluated, as well as showing the importance of hydrogen bonding and pi (π) interactions for the active sites foreseen for each target. Conclusion: The results suggest that P. sprucei quassinoids may interact with 3CLpro and RdRp targets. In vitro and in vivo experiments are needed to confirm the results of molecular docking and investigate the risks of using P. sprucei as a medicinal plant against COVID-19.